The warlock - Scott, Michael, 1959- (New York : Delacorte Press, 2011)
With Scatty, Joan of Arc, Saint Germain, Palamedes, and Shakespeare all in Danu Talis, Sophie is on her own with the ever-weakening Nicholas and Perenelle Flamel. She must depend on Niten to help her find an immortal to teach her Earth Magic. The surprise is that she will find her teacher in the most ordinary of places.
Keywords: Flamel, Nicolas, -- d. 1418 -- Juvenile fiction; Dee, John, -- 1527-1608 -- Juvenile fiction; Machiavelli, Niccol,̣ -- 1469-1527 -- Juvenile fiction; Alchemists -- Juvenile fiction; Magic -- Juvenile fiction; Supernatural -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Twins -- Juvenile fiction; San Francisco (Calif.) -- Juvenile fiction; Fantasy fiction